Identification of Novel Formyl Peptide Receptor-Like 1 Agonists that Induce Macrophage Tumor Necrosis Factor α Production - Schepetkin, Igor A. (2008)
Development of immunomodulatory agents that enhance innate immune responses represents a promising strategy for combating infectious diseases. In the present studies, we screened a series of 71 arylcarboxylic acid hydrazide derivatives for their ability to induce macrophage tumor necrosis factor α (TNF-α) production and identified 6 such compounds, including one compound previously shown to be a formyl peptide receptor (FPR/FPRL1) agonist. The two most potent compounds [Compound 1: nicotinic acid [5-(3-bromophenyl)-2-furyl]methylene-hydrazide; Compound 2: 4-fluoro-benzoic acid [5-(3-trifluoromethyl-phenyl)-2-furyl]methylene-hydrazide] were selected for further analysis. These compounds induced de novo production of TNF-α in a dose- and time-dependent manner in human and murine monocyte/macrophage cell lines and in primary macrophages. These compounds also induced mobilization of intracellular Ca(2+), production of reactive oxygen species, and chemotaxis in human and murine phagocytes. Induction of macrophage TNF-α production was pertussis toxin-sensitive, and analysis of the cellular target of these compounds showed that they were FPRL1-specific agonists and that this response was blocked by FPR/FPRL1 and FPRL1-specific antagonists. Additionally, pharmacophore modeling showed a high degree of similarity for low-energy conformations of these two compounds to the current pharmacophore model for FPR ligands (Edwards et al., 2005). Overall, these compounds represent novel FPRL1 agonists that induce TNF-α, a response distinct from those induced by other known FPR and FPRL1 agonists.